Nuclear waste glass curing material with anti-radiation stability and durability and preparation method thereof

The polycrystalline phase composite nuclear waste glass curing material prepared through high-temperature melting and annealing treatment solves the long-term stability and safety of radionuclides in high-level waste, and achieves effective inclusion and stability of radionuclides, significantly reducing the harm of nuclear waste to the environment.

CN119898963AInactive Publication Date: 2025-04-29LUOYANG INST OF SCI & TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510396670.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2025-04-29
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing nuclear waste treatment technologies are difficult to effectively solve the long-term stability and safety of radionuclides in high-level wastes, especially those with long half-life nuclides such as Phenol-237 and Plutonium-239.

Method used

By melting and annealing materials such as SiO2, PbO, Al2O3, Na2O, K2O, BaO, Cd2O2, CeO2, molybdenum calcium ore powder, cesium garnet powder and other materials, a nuclear waste glass curing material with a polycrystalline phase composite structure was prepared to enhance its radiation resistance and durability.

Benefits of technology

It has achieved effective inclusion and stability of radionuclides in high-level waste, improved the corrosion resistance and radiation resistance of glass cured materials, and significantly reduced the harm of nuclear waste to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the field of nuclear waste treatment, and discloses a nuclear waste glass curing material with anti-radiation stability and durability and a preparation method of the nuclear waste glass curing material, glass curing raw materials for radioactive nuclear waste glass curing treatment are mainly prepared from SiO2, PbO, Al2O3, Na2O, K2O, BaO, Cd2O2, CeO2, molybdenum calcium ore powder and pollucite powder which are excellent in performance according to a certain weight part, and the glass curing raw materials are mixed according to a certain weight part ratio. Through grinding, melting, cooling molding, annealing heat preservation and natural cooling processes, the prepared glass raw material for radioactive nuclear waste glass curing treatment is excellent in performance and has the characteristics of good radiation inclusiveness, durability and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nuclear waste treatment, and in particular to a nuclear waste glass solidification material with radiation resistance stability and durability and a preparation method thereof. Background Art

[0002] With the development of world energy, the limitations of fossil fuels are becoming more and more obvious. New energy is an important component to effectively delay the energy crisis. Although renewable energy such as solar energy, wind energy, and tidal energy have a reputation for zero pollution, they cannot meet my country's large-scale industrial electricity demand in the short term. Nuclear energy is a highly efficient energy with high energy density, which meets the strategic needs of my country's development. However, the treatment of nuclear waste left after nuclear energy is currently difficult. The difficulty, heavy pollution, and easy leakage have become important problems restricting the development of nuclear energy. High-level waste contains radioactive nuclides such as neptunium, plutonium, americium, technetium, iodine, strontium, and cesium. Its main characteristics are high radiation levels, long half-life periods, high toxicity of nuclides, and heat generation. The radioactive specific activity of high-level waste (liquid waste) is 3.7×109Bq / L. The half-lives of neptunium-237 and plutonium-239 are all over 100,000 years. They cannot be degraded or eliminated by ordinary physical, chemical or biological methods. They can only rely on their own radioactive decay to slowly reduce their harm. Different from the traditional "up to the sky and into the earth", nuclear waste glass solidification treatment is the only scalable and commercial treatment method to achieve safe treatment of nuclear waste. Here, how to better contain radioactive elements and achieve higher performance stability and durability has become a key research goal.

[0003] Therefore, we can rely on the unique inclusiveness of glass, but the nuclear waste glass solidification technology requires special glass raw materials. In the high-temperature treatment furnace of nuclear waste, the glass raw materials are melted together with the nuclear waste, and melted again into glass liquid at high temperature. After process treatment, it finally forms a vitrified solid, completing the treatment of nuclear waste, thereby protecting the ecological environment and promoting the development of my country and industry. my country's process route for high-level waste management adopts the "glass solidification-geological disposal" method. The safe disposal of high-level waste glass solidification treatment can fill the domestic gap and is of great significance to the development of my country's nuclear waste treatment project. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a nuclear waste glass solidification material with radiation resistance stability and durability and a preparation method thereof. The glass solidification raw materials used for the glass solidification treatment of radioactive nuclear waste are mainly SiO2, PbO, Al2O3, Na2O, K2O, BaO, Cd2O2, CeO2, molybdenum calcium ore powder, and cesium garnet powder with excellent performance in certain weight proportions, which are subjected to grinding, melting, cooling and forming, annealing and heat preservation, and natural cooling processes. The glass raw materials used for the glass solidification treatment of radioactive nuclear waste have excellent performance, good radiation tolerance, durability, and corrosion resistance.

[0005] The present invention reconstructs the glass formula through multiple heavy metal elements, so that it has the excellent properties of multiple elements and forms a polycrystalline phase complex, while also increasing the radiation resistance, corrosion resistance and radiation tolerance; the preparation process is also relatively simple, the performance is excellent, and the problem of radiation pollution from radioactive waste can be well solved.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is: A nuclear waste glass solidification material with radiation resistance stability and durability, comprising: the weight proportions of original materials are: SiO2: 40-42 parts, PbO: 28-34 parts, Al2O3: 8-12 parts, Na2O: 5-9 parts, K2O: 3-15 parts, BaO: 1-1.2 parts, Cd2O2: 0.3-0.5 parts, CeO2: 0.1-0.25 parts, CaMoO4: 0.8-5 parts, CsAlSi2O6: 0.2-1 parts.

[0007] The purity of SiO2 is ≥99% and the particle size is 200 mesh.

[0008] The purity of PbO is ≥99% and the particle size is ≤3μm.

[0009] The purity of Al2O3 is ≥99% and the particle size is 200 mesh.

[0010] The purity of Na2O is ≥99% and the particle size is ≤5μm.

[0011] The purity of K2O is ≥99% and the particle size is ≤5μm.

[0012] The purity of BaO is ≥99% and the particle size is ≤10μm.

[0013] The purity of Cd2O2 is ≥95% and the particle size is ≤5μm.

[0014] The purity of CeO2 is ≥98% and the particle size is ≤3μm.

[0015] The purity of CaMoO4 is ≥90% and the particle size is ≤5μm.

[0016] The purity of CsAlSi2O6 is ≥90% and the particle size is ≤3μm.

[0017] A method for preparing a nuclear waste glass solidification material with radiation resistance stability and durability comprises the following steps: Step 1: Mix the raw materials at high temperature to prepare the base material; SiO2, PbO, Al2O3, Na2O, K2O, BaO, Cd2O2, CeO2, molybdenum calcium ore powder and cesium garnet powder are mixed and ground, and after grinding for 8-12 hours, they are allowed to stand for 1 hour, and then added into a melting furnace according to the above weight proportions, and melted into a molten liquid at a high temperature in the melting furnace. After the molten liquid is clarified and homogenized, it flows into a working pool to obtain a substrate; Step 2: preparing glass raw materials; The substrate is led into a forming tank, the forming temperature is 1050-1200°C, the annealing temperature is 500-550°C, and a glass solid is obtained; the glass solid is sent to an annealing furnace for annealing treatment, the temperature of the high temperature zone of the annealing furnace is controlled to be 550-580°C, and the time is ≥20min; the temperature of the low temperature zone of the annealing furnace is controlled to be 300-350°C, and the time is ≥180min; the temperature of the insulation zone of the annealing furnace is reduced from 300°C to 20-25°C along the discharge direction, and the insulation time is ≥100min; hot air is introduced into the annealed glass, the hot air temperature is ≥300°C, the wind speed is 1m / s, and the ventilation time is 30min; after ventilation and shaping, the nuclear waste glass solidified material with radiation stability and durability is obtained, and is stored in a room temperature, dry, windless, and dust-free environment for natural air drying or high-pressure gas air drying.

[0018] In step one, by melting SiO2, PbO, Al2O3, Na2O, K2O, BaO, Cd2O2, CeO2, molybdenum calcium ore powder and cesium garnet powder at high temperature, not only the melting and reorganization are achieved, but also the bonding between the particles is further enhanced during the melting process, thereby increasing the density of the glass to a certain extent and improving the inclusiveness of the glass.

[0019] SiO2 is the main component of glass. Its main function is to give glass a basic skeleton and shape, forming a glass structure. During the high-temperature melting process, it reduces the crystallization tendency of glass and increases the viscosity of the glass liquid to obtain higher stability, thereby being able to resist the erosion of acids, alkalis and other chemical reactions, improving the stability of the glass body after vitrification of nuclear waste and reducing the harm of nuclear waste to the environment. Appropriately reducing the proportion of SiO2 can make the glass easier during the melting, clarification and homogenization processes, reduce energy consumption and save costs.

[0020] PbO is an important radiation shielding material. Its high density and high atomic number make it perform well in gamma ray shielding. The addition of PbO can form a stable Pb-O bond, enhance the structural stability of the glass network, and thus improve the chemical durability of the glass. In addition, an appropriate amount of PbO can improve the elasticity and thermal expansion coefficient of the glass. The linking of the Pb-O bond during the reaction with SiO2 promotes the formation of the overall glass, which can better contain nuclear waste and form a stable glass body, shielding nuclear waste radiation and reducing harm to the environment. PbO reacts with SiO2 and Al2O3 during the melting process to form lead silicates (such as PbSiO3) or lead aluminates (such as PbAl2O4). These compounds will form a eutectic structure when cooled. This mixed structure can effectively improve the glass body's tolerance and carrying capacity for internal nuclear waste, protect the ecological environment to a certain extent, and promote the development of my country's nuclear industry.

[0021] The addition of Al2O3 can enhance the chemical stability of glass, reduce the erosion of glass on refractory materials, and improve its water resistance and corrosion resistance. By forming an Al-O tetrahedral structure, it combines with alkali metal ions in the glass to reduce the number of non-bridging oxygen, thereby reducing the crystallization tendency of the glass and improving the chemical stability. Secondly, Al2O3 participates in and forms a stable network structure, effectively improving the mechanical strength, hardness, crack resistance and impact resistance of the glass, reducing the brittleness of the glass, and improving toughness. It can significantly improve the overall stability and durability of the waste-containing glass. Al2O3 and SiO2 generate mullite (3Al2O3·2SiO2) at high temperatures. Its whisker structure can delay particle aggregation, significantly improve the thermal stability of the glass, improve durability, and prolong the action time of the glass, effectively solving the difficulties in solving nuclear waste and the serious pollution to the environment. In the SiO2-Al2O3-PbO system, the material reaction can form an [AlO4]⁻ tetrahedral reinforced glass network to improve the crystallization resistance.

[0022] Na2O and K2O mainly play a role in fluxing, lowering the melting temperature of glass, increasing the fluidity of glass liquid, promoting glass formation and clarification, and reducing energy consumption. An appropriate amount of K2O can work synergistically with Na2O to improve the overall performance of glass. Na2O and K2O can act as glass network modifiers and react with SiO2 to form silicates such as Na2SiO3 and K2SiO3. K2O is more likely to form stable K2SiO3 at high temperatures. These reactions make the glass more stable and more durable.

[0023] BaO can promote the formation of crystalline phase in glass, thereby improving the structural stability and mechanical properties of glass. During the melting process, it can improve the thermal stability of glass, reduce the melting temperature of glass, and inhibit the decline of devitrification resistance of glass, thereby improving the corrosion resistance. In the molten state, the mixed alkali effect promotes the formation of Na2O-K2O-BaO, reduces the melt viscosity, and promotes uniform wrapping of waste liquid. The addition of BaO can also reduce the softening point, promote densification, inhibit grain coarsening, and improve material strength.

[0024] Cd2O2 can be used as a transition metal ion to change the chemical composition and structural characteristics of glass. The formation of special chemical bonds helps optimize the function of the glass. Cd2O2 can be converted into CdO (cubic phase) at high temperature. After annealing, CeO2 can be used as a stabilizer to improve the radiation resistance and chemical stability of the glass, absorb radiation, and enhance the radiation protection performance of the glass. CdO2-CeO2 high field strength ions (such as Ce 4+ ) Enhance network aggregation and inhibit radiation damage.

[0025] Molybdenum calcium ore powder can effectively improve the corrosion resistance of glass and improve its mechanical properties and high temperature performance. It can effectively promote the phase separation and precipitate formation of glass during the melting process. During the annealing and heat preservation stage, the temperature drops and the phase separation structure is formed. 6+ Entering the silicon-rich phase improves chemical stability. CaMoO4 is not easily decomposed during melting and annealing, and will form composite oxides with Al2O3 and SiO2 to maintain the stability of the glass structure.

[0026] Cesium garnet powder can promote crystal growth and density, enhance the thermal and chemical stability of glass, and thus improve its service life in high temperature and harsh environments, and ensure long-term safety. Cs⁺ in cesium garnet powder (CsAlSi2O6) undergoes ion exchange with Pb²⁺ in glass to form a Cs-Pb composite structure, which can effectively reduce the leaching rate of glass.

[0027] Therefore, the nuclear waste glass solidification material with radiation resistance stability and durability of the present invention is formed by a series of preparation methods of the raw materials in the present invention. The crystal phase of the original material changes to form a polycrystalline phase complex, including: lead silicate (such as PbSiO3), lead aluminate (such as PbAl2O4), mullite (3Al2O3·2SiO2), Na2SiO3, K2SiO3, Na2O-K2O-BaO, CdO2-CeO2, CaMoO4, Cs-Pb, etc.; the formed polycrystalline phase complex is 137 Cs and 239 The leaching rate of Pu nuclide is less than 1×10 -5cm / d, with good radiation tolerance, durability and corrosion resistance.

[0028] Chemical reactions between the original materials form different chemical bonds, which have a significant impact on the formation of the final glass body, the degree of nuclear waste inclusion, the density, and the upper limit of the time the final waste-containing glass body can maintain normal shielding effects. The nuclear waste glass solidification material has a significant solidification effect and strong corrosion resistance.

[0029] The present invention utilizes the excellent radiation protection performance of heavy metal elements and fuses them with traditional glass raw materials to form a dense glass structure with a composite crystal phase, further increasing the stability of material properties and achieving an improvement in the containment performance of radioactive waste, which is technically outstandingly advanced.

[0030] The present invention improves the stability and durability of high borosilicate glass in a high flux neutron radiation environment by introducing heavy metals, thereby improving the tolerance and load capacity of nuclear waste glass solidification. It has a wide range of promotion and application prospects in the field of nuclear waste treatment and is suitable for the solidification treatment of radioactive nuclear waste in my country.

[0031] The present invention prepares glass raw materials by melting SiO2, PbO, Al2O3, Na2O, K2O, BaO, Cd2O2, CeO2, molybdenum calcium ore powder, and cesium garnet powder, cooling the molten product to form it, and annealing and heat preservation. SiO2, PbO, Al2O3, Na2O, K2O, BaO, Cd2O2, CeO2, molybdenum calcium ore powder, and cesium garnet powder are melted at high temperature to enhance the bonding degree of different materials and strengthen the recombination bonding between molecules; The preparation process of the invention is relatively simple, and the prepared glass raw material for radioactive nuclear waste glass solidification treatment has the characteristics of good radiation tolerance, high melting point and high density.

[0032] The glass solidifying material prepared by the present invention has a uniform glass body without abnormalities and inclusions, has impact resistance and strong resistance to gamma radiation, and has strict requirements on thermal conductivity, conversion temperature, liquidus temperature and nuclide leaching rate. In order to prevent the escape of a large amount of nuclides (or contaminating elements), the melting point of the glass body is controlled at 1150-1250°C. 137 Cs and 239 The leaching rate of Pu nuclide is less than 1×10 -5 cm / d, the density of the solidified material is greater than 2.5g / cm 3 The impact resistance is less than or equal to 12cm 2 / J, the overall compressive strength is greater than 74MPa. DETAILED DESCRIPTION

[0033] The present invention will be further described in detail below with reference to specific embodiments.

[0034] The embodiment of the present invention provides a nuclear waste glass solidification material with radiation resistance stability and durability, wherein the purity of SiO2 is ≥99% and the particle size is 200 mesh. The purity of PbO is ≥99% and the particle size is ≤3μm. The purity of Al2O3 is ≥99% and the particle size is 200 mesh. The purity of Na2O is ≥99% and the particle size is ≤5μm. The purity of K2O is ≥99% and the particle size is ≤5μm. The purity of BaO is ≥99% and the particle size is ≤10μm. The purity of Cd2O2 is ≥95% and the particle size is ≤5μm. The purity of CeO2 is ≥98% and the particle size is ≤3μm. The purity of CaMoO4 is ≥90% and the particle size is ≤5μm. The purity of CsAlSi2O6 is ≥90% and the particle size is ≤3μm.

[0035] Example 1

[0036] A nuclear waste glass solidification material with radiation resistance stability and durability, comprising: the weight proportions of original materials are: SiO2: 40 parts, PbO: 34 parts, Al2O3: 12 parts, Na2O: 8 parts, K2O: 3 parts, BaO: 1 part, Cd2O2: 0.3 parts, CeO2: 0.1 parts, CaMoO4: 0.8 parts, CsAlSi2O6: 0.8 parts.

[0037] The preparation method is: Step 1: Mix the raw materials at high temperature to prepare the base material; SiO2, PbO, Al2O3, Na2O, K2O, BaO, Cd2O2, CeO2, molybdenum calcium ore powder and cesium garnet powder are mixed and ground, and after grinding for 8 hours, they are allowed to stand for 1 hour, and then added into a melting furnace according to the above weight proportions, and melted into a molten liquid at a high temperature in the melting furnace. After the molten liquid is clarified and homogenized, it flows into a working pool to obtain a substrate; Step 2: preparing glass raw materials; The substrate is led into a forming tank, the forming temperature is 1050°C, the annealing temperature is 550°C, and a glass solid is obtained; the glass solid is sent to an annealing furnace for annealing treatment, the temperature of the high temperature zone of the annealing furnace is controlled to be 580°C, the time is 20 minutes; the temperature of the low temperature zone of the annealing furnace is controlled to be 350°C, the time is 180 minutes; the temperature of the insulation zone of the annealing furnace is reduced from 300°C to 25°C along the discharge direction, and the insulation time is 100 minutes; hot air is introduced into the annealed glass, the hot air temperature is 300°C, the wind speed is 1m / s, and the ventilation time is 30 minutes; after ventilation and shaping, this nuclear waste glass solidification material with radiation stability and durability is obtained, and is stored in a room temperature, dry, windless, dust-free environment for natural air drying or high-pressure gas air drying.

[0038] Example 2

[0039] A nuclear waste glass solidification material with radiation resistance stability and durability, comprising: the weight proportions of original materials are: SiO2: 42 parts, PbO: 28 parts, Al2O3: 8 parts, Na2O: 5 parts, K2O: 10 parts, BaO: 1.2 parts, Cd2O2: 0.4 parts, CeO2: 0.2 parts, CaMoO4: 5 parts, CsAlSi2O6: 0.2 parts.

[0040] The preparation method is: Step 1: Mix the raw materials at high temperature to prepare the base material; SiO2, PbO, Al2O3, Na2O, K2O, BaO, Cd2O2, CeO2, molybdenum calcium ore powder and cesium garnet powder are mixed and ground, and after grinding for 12 hours, they are allowed to stand for 1 hour, and then added into a melting furnace according to the above weight proportions, and melted into a molten liquid at a high temperature in the melting furnace. After the molten liquid is clarified and homogenized, it flows into a working pool to obtain a substrate; Step 2: preparing glass raw materials; The substrate is led into a forming tank, the forming temperature is 1200°C, the annealing temperature is 500°C, and a glass solid is obtained; the glass solid is sent to an annealing furnace for annealing treatment, the temperature of the high temperature zone of the annealing furnace is controlled to be 580°C, the time is 30 minutes; the temperature of the low temperature zone of the annealing furnace is controlled to be 300°C, the time is 200 minutes; the temperature of the insulation zone of the annealing furnace is reduced from 300°C to 25°C along the discharge direction, and the insulation time is 150 minutes; hot air is introduced into the annealed glass, the hot air temperature is 350°C, the wind speed is 1m / s, and the ventilation time is 30 minutes; after ventilation and shaping, this nuclear waste glass solidification material with radiation stability and durability is obtained, and is stored in a room temperature, dry, windless, dust-free environment for natural air drying or high-pressure gas air drying.

[0041] Example 3

[0042] A nuclear waste glass solidification material with radiation resistance stability and durability, comprising: the weight proportions of original materials are: SiO2: 41 parts, PbO: 30 parts, Al2O3: 10 parts, Na2O: 9 parts, K2O: 3 parts, BaO: 1 part, Cd2O2: 0.5 parts, CeO2: 0.1 parts, CaMoO4: 5 parts, CsAlSi2O6: 0.4 parts.

[0043] The preparation method is: Step 1: Mix the raw materials at high temperature to prepare the base material; SiO2, PbO, Al2O3, Na2O, K2O, BaO, Cd2O2, CeO2, molybdenum calcium ore powder and cesium garnet powder are mixed and ground, and after grinding for 10 hours, they are allowed to stand for 1 hour, and then added into a melting furnace according to the above weight proportions, and melted into a molten liquid at a high temperature in the melting furnace. After the molten liquid is clarified and homogenized, it flows into a working pool to obtain a substrate; Step 2: preparing glass raw materials; The substrate is led into a forming tank, the forming temperature is 1100°C, the annealing temperature is 500°C, and a glass solid is obtained; the glass solid is sent to an annealing furnace for annealing treatment, the temperature of the high temperature zone of the annealing furnace is controlled to be 580°C, the time is 25 minutes; the temperature of the low temperature zone of the annealing furnace is controlled to be 300°C, the time is 250 minutes; the temperature of the insulation zone of the annealing furnace is reduced from 300°C to 20°C along the discharge direction, and the insulation time is 200 minutes; hot air is introduced into the annealed glass, the hot air temperature is 400°C, the wind speed is 1m / s, and the ventilation time is 30 minutes; after ventilation and shaping, this nuclear waste glass solidification material with radiation stability and durability is obtained, and is stored in a room temperature, dry, windless, dust-free environment for natural air drying or high-pressure gas air drying.

[0044] Example 4

[0045] A nuclear waste glass solidification material with radiation resistance stability and durability, comprising: the weight proportions of original materials are: SiO2: 42 parts, PbO: 29 parts, Al2O3: 9 parts, Na2O: 8 parts, K2O: 8 parts, BaO: 1.2 parts, Cd2O2: 0.5 parts, CeO2: 0.1 parts, CaMoO4: 1.2 parts, CsAlSi2O6: 1 part.

[0046] The preparation method is: Step 1: Mix the raw materials at high temperature to prepare the base material; SiO2, PbO, Al2O3, Na2O, K2O, BaO, Cd2O2, CeO2, molybdenum calcium ore powder and cesium garnet powder are mixed and ground, and after grinding for 12 hours, they are allowed to stand for 1 hour, and then added into a melting furnace according to the above weight proportions, and melted into a molten liquid at a high temperature in the melting furnace. After the molten liquid is clarified and homogenized, it flows into a working pool to obtain a substrate; Step 2: preparing glass raw materials; The substrate is led into a forming tank, the forming temperature is 1200°C, the annealing temperature is 550°C, and a glass solid is obtained; the glass solid is sent to an annealing furnace for annealing treatment, the temperature of the high temperature zone of the annealing furnace is controlled to be 580°C, the time is 20 minutes; the temperature of the low temperature zone of the annealing furnace is controlled to be 350°C, the time is 200 minutes; the temperature of the insulation zone of the annealing furnace is reduced from 300°C to 25°C along the discharge direction, and the insulation time is 100 minutes; hot air is introduced into the annealed glass, the hot air temperature is 300°C, the wind speed is 1m / s, and the ventilation time is 30 minutes; after ventilation and shaping, this nuclear waste glass solidification material with radiation stability and durability is obtained, and is stored in a room temperature, dry, windless, dust-free environment for natural air drying or high-pressure gas air drying.

[0047] The performance indicators of the nuclear waste glass solidified materials with radiation resistance stability and durability of Examples 1, 2, 3 and 4 are as follows:

[0048] The glass raw material prepared by the present invention for the glass solidification treatment of radioactive nuclear waste has excellent containment performance and corrosion resistance. Compared with other preparation methods, this preparation method has the following advantages: the preparation process only requires melting, molding, annealing and heat preservation processes, and the process is simple.

Claims

1. A nuclear waste glass solidification material with radiation resistance stability and durability, characterized by: include: The weight proportions of the original materials are: SiO2: 40-42 parts, PbO: 28-34 parts, Al2O3: 8-12 parts, Na2O: 5-9 parts, K2O: 3-15 parts, BaO: 1-1.2 parts, Cd2O2: 0.3-0.5 parts, CeO2: 0.1-0.25 parts, CaMoO4: 0.8-5 parts, CsAlSi2O6: 0.2-1 parts; the obtained nuclear waste glass solidification material is a polycrystalline phase complex, comprising: PbSiO3, PbAl2O4, 3Al2O3·2SiO2, Na2SiO3, K2SiO3, Na2O-K2O-BaO, CdO2-CeO2, CaMoO4, Cs-Pb.

2. The nuclear waste glass solidification material with radiation resistance stability and durability according to claim 1, characterized in that: SiO2 purity ≥99%, particle size 200 mesh; PbO purity ≥99%, particle size ≤3μm; Al2O3 purity ≥99%, particle size 200 mesh; Na2O purity ≥99%, particle size ≤5μm.

3. The nuclear waste glass solidification material with radiation resistance stability and durability according to claim 1, characterized in that: K2O purity ≥99%, particle size ≤5μm; BaO purity ≥99%, particle size ≤10μm; Cd2O2 purity ≥95%, particle size ≤5μm.

4. The nuclear waste glass solidification material with radiation resistance stability and durability according to claim 1, characterized in that: The purity of CeO2 is ≥98%, and the particle size is ≤3μm; the purity of CaMoO4 is ≥90%, and the particle size is ≤5μm; the purity of CsAlSi2O6 is ≥90%, and the particle size is ≤3μm.

5. The method for preparing a nuclear waste glass solidification material with radiation resistance stability and durability according to claim 1, characterized in that: The following steps are involved: Step 1: Mix the raw materials at high temperature to prepare the base material; SiO2, PbO, Al2O3, Na2O, K2O, BaO, Cd2O2, CeO2, molybdenum calcium ore powder and cesium garnet powder are mixed and ground, and after grinding for 8-12 hours, they are allowed to stand for 1 hour, and then added into a melting furnace according to the above weight proportions, and melted into a molten liquid at a high temperature in the melting furnace. After the molten liquid is clarified and homogenized, it flows into a working pool to obtain a substrate; Step 2: preparing glass raw materials; The substrate is led into a forming tank, the forming temperature is 1050-1200°C, the annealing temperature is 500-550°C, and a glass solid is obtained; the glass solid is sent to an annealing furnace for annealing treatment, the temperature of the high temperature zone of the annealing furnace is controlled to be 550-580°C, and the time is ≥20min; the temperature of the low temperature zone of the annealing furnace is controlled to be 300-350°C, and the time is ≥180min; the temperature of the insulation zone of the annealing furnace is reduced from 300°C to 20-25°C along the discharge direction, and the insulation time is ≥100min; hot air is introduced into the annealed glass, the hot air temperature is ≥300°C, the wind speed is 1m / s, and the ventilation time is 30min; after ventilation and shaping, the nuclear waste glass solidified material with radiation stability and durability is obtained, and is stored in a room temperature, dry, windless, and dust-free environment for natural air drying or high-pressure gas air drying.

Citation Information

Patent Citations

  • Method for preparing high-radioactivity nuclear waste glass solidified base material

    CN103265169A

  • Radiation shielding glass and preparation method thereof

    CN106007366A

  • Radioactive waste solidification base material and preparation method of solidified glass

    CN110335695A

  • Radiation-resistant glass with gamma-ray shielding and neutron protection functions and preparation method thereof

    CN117585899A

  • Vitrifying material for solidifying waste and waste-solidified glass

    JP1998167754A